Influences of environmental stressors on autonomic function in 12‐month‐old infants: understanding early common pathways to atypical emotion regulation and cognitive performance. (1st July 2019) - Wass, Sam V.; Smith, Celia G.; Daubney, Katie R.; Suata, Zeynep M.; Clackson, Kaili; Begum, Abdul; Mirza, Farhan U.
Abstract : Background: Previous research has suggested that children exposed to more early‐life stress show worse mental health outcomes and impaired cognitive performance in later life, but the mechanisms subserving these relationships remain poorly understood. Method: Using miniaturised microphones and physiological arousal monitors (electrocardiography, heart rate variability and actigraphy), we examined for the first time infants' autonomic reactions to environmental stressors (noise) in the home environment, in a sample of 82 12‐month‐old infants from mixed demographic backgrounds. The same infants also attended a laboratory testing battery where attention‐ and emotion‐eliciting stimuli were presented. We examined how children's environmental noise exposure levels at home related to their autonomic reactivity and to their behavioural performance in the laboratory. Results: Individual differences in total noise exposure were independent of other socioeconomic and parenting variables. Children exposed to higher and more rapidly fluctuating environmental noise showed more unstable autonomic arousal patterns overall in home settings. In the laboratory testing battery, this group showed more labile and short‐lived autonomic changes in response to novel attention‐eliciting stimuli, along with reduced visual sustained attention. They also showed increased arousal lability in response to an emotional stressor. Conclusions: Our results offer new insights into the mechanisms by which environmental noise exposure may confer increased risk of adverse mental health and impaired cognitive performance during later life.